2021
DOI: 10.1136/annrheumdis-2021-220964
|View full text |Cite
|
Sign up to set email alerts
|

Dactylitis is an indicator of a more severe phenotype independently associated with greater SJC, CRP, ultrasound synovitis and erosive damage in DMARD-naive early psoriatic arthritis

Abstract: ObjectiveTo characterise the impact of dactylitis in disease-modifying antirheumatic drug (DMARD)-naive early psoriatic arthritis (PsA).MethodsPatients with early PsA meeting the classification criteria for PsA (CASPAR) were recruited. Clinical outcomes were recorded, and ultrasonography was conducted to assess grey scale (GS) and power Doppler (PD) synovitis, periarticular cortical bone erosions and enthesitis. The cohort was dichotomised by the presence or absence of dactylitis.ResultsOf 177 patients with Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
3
9
1
Order By: Relevance
“…However, for PsA, a definition of severity is still lacking; in 2005, Brockbanck et al proposed dactylitis as a clinical marker of disease severity because of its association with a greater degree of radiological damage [ 19 ]. This concept is in keeping with a recent study in which early PsA patients (DMARDs-naïve) with dactylitis seem to have a greater burden of disease (greater SwJC, TJC, CRP, ultrasound synovitis and erosive damage) [ 20 ] when compared to early PsA patients without dactylitis. Therefore, it could be supposed that EOP is also a marker of severity in PsO, due to the association that we found between EOP and dactylitis.…”
Section: Discussionsupporting
confidence: 80%
“…However, for PsA, a definition of severity is still lacking; in 2005, Brockbanck et al proposed dactylitis as a clinical marker of disease severity because of its association with a greater degree of radiological damage [ 19 ]. This concept is in keeping with a recent study in which early PsA patients (DMARDs-naïve) with dactylitis seem to have a greater burden of disease (greater SwJC, TJC, CRP, ultrasound synovitis and erosive damage) [ 20 ] when compared to early PsA patients without dactylitis. Therefore, it could be supposed that EOP is also a marker of severity in PsO, due to the association that we found between EOP and dactylitis.…”
Section: Discussionsupporting
confidence: 80%
“…Dactylitis, a characteristic feature of PsA, is one of six clinical domains considered in PsA treatment decisions, along with peripheral arthritis, axial disease, enthesitis, skin disease, and nail disease ( 2 ). Dactylitis typically presents as swelling of the whole digit, with inflammation in the joints, soft tissues, and tendon sheaths ( 3 , 4 , 5 , 6 ). Although dactylitis can occur in patients with other diseases, it is a hallmark feature of PsA, developing in up to 50% of patients at some point during their disease course, with toes affected more often than fingers ( 5 , 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dactylitis typically presents as swelling of the whole digit, with inflammation in the joints, soft tissues, and tendon sheaths ( 3 , 4 , 5 , 6 ). Although dactylitis can occur in patients with other diseases, it is a hallmark feature of PsA, developing in up to 50% of patients at some point during their disease course, with toes affected more often than fingers ( 5 , 6 , 7 ). Imaging studies in patients with PsA revealed that flexor tenosynovitis with diffuse extra‐tendinous inflammation with an epicenter around accessory pulleys is a characteristic feature of dactylitis pathogenesis, helping to differentiate it from rheumatoid and other forms of arthritis ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dactylitis, defined as a diffuse swelling of a digit (sausage-like digit), is a hallmark clinical feature in psoriatic arthritis (PsA) [1]. Dactylitis is also a marker of clinical severity and joint damage development in PsA [2]. On imaging, particularly on high-resolution ultrasound and magnetic resonance imaging (MRI), dactylitis consists of a variable combination of digital extra-synovial and synovial inflammatory lesions which may be accompanied by intra-or periarticular proliferative and erosive bone changes [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%